2007
DOI: 10.1523/jneurosci.4486-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the NR2B Receptor and CaMKII Modulate Synaptic Plasticity and Spatial Learning

Abstract: The NR2B subunit of the NMDA receptor interacts with several prominent proteins in the postsynaptic density, including calcium/ calmodulin-dependent protein kinase II (CaMKII). To determine the function of these interactions, we derived transgenic mice expressing a ligand-activated carboxy-terminal NR2B fragment (cNR2B) by fusing this fragment to a tamoxifen (TAM)-dependent mutant of the estrogen receptor ligand-binding domain LBD G521R . Here, we show that induction by TAM allows the transgenic cNR2B fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 56 publications
11
132
4
1
Order By: Relevance
“…Those two modes of CaMKII autonomous activity, T286 autophosphorylation and GluN2B binding, could thus have distinct terms and serve different functions inside the spine. The importance of GluN2B NMDAR subunit interaction with ␣CaMKII in synaptic potentiation has been already demonstrated (Barria and Malinow, 2005;Zhou et al, 2007). The functional link between CaMKII and ERK signaling in LTP was suggested by Zhu et al (2002), who showed that the MEK inhibitor PD98095 could affect CaMKII-mediated increase in synaptic insertion of AMPARs.…”
Section: Discussionmentioning
confidence: 90%
“…Those two modes of CaMKII autonomous activity, T286 autophosphorylation and GluN2B binding, could thus have distinct terms and serve different functions inside the spine. The importance of GluN2B NMDAR subunit interaction with ␣CaMKII in synaptic potentiation has been already demonstrated (Barria and Malinow, 2005;Zhou et al, 2007). The functional link between CaMKII and ERK signaling in LTP was suggested by Zhu et al (2002), who showed that the MEK inhibitor PD98095 could affect CaMKII-mediated increase in synaptic insertion of AMPARs.…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that binding of CaMKII to the NR2B subunit is necessary for LTP induction (Barria and Malinow, 2005). More recently, inducible and reversible disruption of NR2B/CaMKII interactions in transgenic mice has been shown to be involved in downregulation of ␣CaMKII autophosphorylation and reduction of LTP in the hippocampus (Zhou et al, 2007). Our data are in agreement with all these previous observations: here, we show that CaMKII inhibition by means of Ant-AIP-2 leads to a disruption of ␣CaMKII/ NR2B complex and to a subsequent reduction of ␣CaMKII and NR2B protein levels at synapses without affecting NR2A subunit localization, and that this molecular event is associated with a decreased LTP induction.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the molecular details of these interactions have been addressed, the physiological function of these interactions still remains to be clarified. Interestingly, recent data have put forward new roles for NMDA receptor-CaMKII complex in synaptic plasticity (Barria and Malinow, 2005;Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of NMDARs, CaMKII binding to the NMDAR subunit, GluN2B, has been shown to be important for induction and maintenance of LTP (Lisman et al, 2002;Barria and Malinow, 2005;Zhou et al, 2007;Sanhueza et al, 2011) and activitydependent new spine outgrowth (Hamilton et al, 2012); interruption of this interaction causes decreased spine density (Gambrill and Barria, 2011). Moreover, CaMKII activation is important for new spine stabilization during experiencedependent plasticity (Wilbrecht et al, 2010).…”
Section: Nmdar Activation and Interaction Of Nmdars With Camkii Are Rmentioning
confidence: 99%